2014
DOI: 10.12691/education-2-12-4
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on Student and their Attitudes toward Statistics Course and Statistical Field

Abstract: The aim of this study was to verify whether there are significant differences between the profiles of the mean score students from a sample of three universities, regarding attitude toward the statistics' course and attitude toward the statistical field. The universities were:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
2
0
4
Order By: Relevance
“…Nevertheless, that value is still acceptable for its reliability because all of the items in its dimension had the validity measure (Hair, Black, Babin, & Anderson, 2014). The difficulty dimension had the lowest reliability coefficient that was in line with (García-Santillán, Escalera-Chávez, Rojas-Kramer, & Pozos-Texon, 2014;Hilton et al, 2004;Schau, 2008;Schau, Dauphinee, Del Vecchio, & Stevens, 1999;Tempelaar, Schim Van Der Loeff, & Guselaers, 2007) in their research.…”
Section: Methodssupporting
confidence: 69%
“…Nevertheless, that value is still acceptable for its reliability because all of the items in its dimension had the validity measure (Hair, Black, Babin, & Anderson, 2014). The difficulty dimension had the lowest reliability coefficient that was in line with (García-Santillán, Escalera-Chávez, Rojas-Kramer, & Pozos-Texon, 2014;Hilton et al, 2004;Schau, 2008;Schau, Dauphinee, Del Vecchio, & Stevens, 1999;Tempelaar, Schim Van Der Loeff, & Guselaers, 2007) in their research.…”
Section: Methodssupporting
confidence: 69%
“…On students' attitude towards statistics, the findings of Onocha [35], Mukherjee [28], Houston et al [19] and Usman [41] as cited by Gbore & Daramola [16] reported that attitude to Mathematics explained more of the total variance than the children intelligence and that attitude of students towards science were linked with some personality factors through relationship with teachers. In another finding on the significance of students attitude towards statistics, Shangodoyin & Lasisi [39] cited that Santillán el al [37], Beins [11], Yala. &Wanjohi [45], Katz &Tomezic [22], Wenglinsky [43] and Evans [12] there were existence of positive correlation among college students attitude toward statistics and their academic performance.…”
Section: Results and Analysismentioning
confidence: 98%
“…The literature (HANNIGAN et al, 2014;WADHWA et al, 2015;ZHANG et al, 2012;SHETTY et al, 2015;BATRA et al, 2014) reports the need for improvements in the teaching of biostatistics. These improvements could increase knowledge and/or training among professionals and would create awareness of the importance of biostatistics in research and clinical work (GARCÍA-SANTILLÁN et al, 2014). However, students' perceptions of statistics must be measured (MILIC et al, 2016).…”
Section: Discussionmentioning
confidence: 99%